Sustainable Wealth: Attracting Foregin Direct Investment through Environmental Regulations in OIC Countries - Azzaki, Muhammad Adnan; Mawardi (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2025)
This study examines the ongoing discourse on whether environmental regulations serve as a barrier or an incentive for foreign direct investment (FDI). The literature presents a divided perspective, with previous studies producing inconsistent findings that have led to ambiguity in empirical evidence. Such disparities often arise from variations in datasets and methodologies employed in earlier research. To resolve these inconsistencies, this research provides a comprehensive empirical assessment of the presumed negative impact of strict environmental policies on FDI in Organization of Islamic Cooperation (OIC) member states. Using a panel dataset comprising 32 OIC countries over the period 2010–2020, the study investigates this intricate relationship. The results, which counter the